A citation study of science education theses at the university of Ibadan, Nigerian (2000)
The economic gloom of the resent years found its way into out tertiary Institutions, especially in the area of developing the collection in the libraries and budget cut as well as exchange rate which has equally affected the procurement of reading materials. The yearly statistics revealed that there was decreased in the number of titles added to the collections during the period under study (Annual report of Kenneth Dike Library): This study aims at finding out the bibliographic patterns of students during this period. The paper is concerned with the theses submitted to the University of Ibadan on science education. It analyses, the information sources of science education researchers. There are about 23 doctoral theses on science education submitted between the year 1987 to 1997. These years were chosen because the impact of the gloom was felt then. By middle 1990’s there was through aids from World Bank. With those aids, research materials were suppose to improve so the question this paper try to ask is: does the bibliographic pattern of research work in 1990s improved over that of 1980s.